Color Your Future: Using the Color Code to Strenghthen Your Character - Taylor Hartman
The author of the acclaimed The Color Code, which discussed personality categorization, offers a sequel explaining the use of the Hartman Character Profile, designed to help people recognize and change unfortunate traits, maximizing their inner potential.